TINJAUAN TEOLOGI ISLAM DI DUNIA - Muarif, Ahmad Syamsul; Yunus, Mohammad (Pusat Penelitian dan Pegabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2019)
The purpose of this article is to find out the paradigm of classical to modern Islamic theology, and how Islamic theology is in North American settings. Classical kalam science is Islamic theology which is more inclined to the theocentric or divine discussion which is the subject of its discussion. Theology of modern kalam theology of Islam is a system of values ??that are divine, but from a sociological point of view, it is a phenomenon of civilization, culture, and social reality in human life. Theology needs to be improved among North American Muslims to protect the community against internal divisions and disputes and to defend Muslims from the challenges and provocations of the strength of outside agencies, whether secular culture and institutions, institutions or Christian Da'wah. At the very least theological discourse needs to be revived and expanded if it is only intended to be apologetic, namely to maintain Islamic faith and order in a free market regarding ideas and beliefs that are not normally done by Muslim immigrants. Classical and modern Islamic theology in essence is only for the purpose of apologetics.